Laminoplasty is relevant for degenerative cervical spondylolisthesis when there is little risk of postoperative excessive kyphosis during neck flexion. (May 2023) - Funaba, Masahiro; Suzuki, Hidenori; Imajo, Yasuaki; Nishida, Norihiro; Fujimoto, Kazuhiro; Ikeda, Hiroaki; Sakai, Takashi
Highlights: The aim of this study is to elucidate factors associated with the outcome of laminoplasty for degenerative cervical spondylolisthesis. There was no significant difference in background and preoperative neurological status, but outcome of laminoplasty were significantly inferior in the degenerative cervical spondylolisthesis group. Multivariate logistic analysis revealed that only postoperative C2-7 angle during neck flexion was associated with a good outcome. In the multivariate regression analysis, the preoperative C2-7 angle at neutral and during flexion positively correlated with the postoperative C2-7 angle during flexion. Abstract: Background: Elderly patients with degenerative cervical myelopathy frequently have severe symptoms due to spondylolisthesis. The effectiveness of laminoplasty for degenerative cervical spondylolisthesis (DCS) is an important question. Objective: The aim of this study is to elucidate factors associated with the outcome of laminoplasty for DCS. Method: Eighty-nine patients with cervical spondylotic myelopathy (CSM) who underwent laminoplasty without instrumented posterior fusion were enrolled. Positive spondylolisthesis was defined as more than 2 mm during neck flexion or extension, from this, 46 DCS cases and 43 non-DCS cases were classified. Radiological parameters, including cervical alignment, balance, range of motion, and slippage along with the Japanese Orthopedic Association (JOA) score, were obtained before and 1 year after surgery. Factors associated with good surgical outcomes for DCS were analyzed using multivariate logistic analysis. Results: There were no significant differences in background and preoperative JOA score, but the DCS group recovery rate was significantly less (42% vs 53%). Multivariate logistic analysis revealed only the postoperative C2-7 angle during neck flexion was associated with a favorable outcome for DCS (P = 0.0039, Odds ratio: 1.49, 95% CI: 1.14–1.94). Multivariate regression analysis positively correlated the preoperative C2-7 angle in neutral and during flexion with the postoperative C2-7 angle during flexion. Conclusion: The major factor related to poor outcome was the magnitude of postoperative kyphotic C2-7 angle during neck flexion. Slippage was not directly related to outcome and postoperative cervical alignment. Caution is recommended for surgeons performing laminoplasty on patients with risk factors for postoperative excessive kyphotic C2-7 angle during flexion.